Fetal Medicine and the Pregnant Woman - Wasserman, David (The Hastings Center report, 2018)
In coming decades, fetal medicine may become a routine part of reproductive care. The measures pregnant women now take to protect fetal health are largely generic, like restricting their diets and using supplements. Relatively few interventions are based on specific conditions revealed by ultrasound or genetic testing. A recent finding, though, may herald a dramatic rise in “personalized” fetal medicine: certain drugs already approved by the Food and Drug Administration can apparently boost neural growth in fetuses with Down syndrome, improving cognitive functioning in the future child. Many more condition-specific findings are likely in the near future. But as commentators have frequently observed about prenatal testing, technologies that appear to increase reproductive options also complicate and constrain them.